Nutritional analysis of noodles with and without the additional of Pereskia aculeata - ZEM, Luciele Milani; HELM, Cristiane Vieira; KOEHLER, Henrique Soares; ZUFFELLATO-RIBAS, Katia Christina (Revista Eletrônica Científica da UERGS, 2019)
Pereskia aculeata Mill. is a cactaceous, popularly known as ora-pro-nobis, considered a native and non-endemic vegetables besides being rich in protein, fiber, iron and calcium, among others. This work aimed to study the chemical composition of noodles prepared with the incorporation of dry leaves flour, stems and fresh leaves of Pereskia aculeata, to identify and quantify the nutrients and minerals present. Four recipes were tested: traditional noodles with flour; noodles with incorporating flour from dried leaves; noodles with leaves flour incorporation + stem; noodles with incorporation of fresh leaves. The following analyzes were carried out in a completely randomized design with three replications, and data expressed in percentage in wet and dry basis (g 100g-1): moisture, ash, protein, fiber, lipids, total carbohydrates, total caloric value and minerals. Among the tested recipes, it was concluded that the noodles with incorporating flour dried leaves of Pereskia aculeata showed the best moisture, ash, lipids, proteins, fibers and lower total caloric values. Furthermore, it showed the best results for all analyzed minerals, thus the better nutritional quality.